Unilateral mandibular central giant cell granuloma in a child: a case report - Ghosh, Debadrita; Kumar, Arvind; Mukherjee, Chitrita G.; Verma, Navin K. (International Journal of Research in Medical Sciences, 2025)
At the Department of Pedodontics of Buddha Institute of Dental Sciences and Hospital (BIDSH), an 11-year-old girl presented with a main complaint of widespread edema measuring 2×3 cm along her left cheek. It was really hard and not at all sensitive. "The lymph nodes in the left submental region and the submandibular region were soft, sensitive, movable, and palpable. Located in the lower left vestibule, an intra-oral growth measuring approximately 4 into 4 cm was observed. A destructive lesion stretching from the lower canine region on the right side to the lower central incisor on the left was shown in the computed tomography (CT) 3D reconstruction image. The diagnosis of central giant cell granuloma was confirmed by the histopathology of the incisional biopsy, which showed mostly sheets of spindle to ovoid fibroblastic cells intermingled with gigantic cells that looked like osteoclasts. Under general anesthesia, the patient underwent marsupalization and enucleation. Histopathology was then used to confirm the diagnosis.